1996
DOI: 10.1111/j.1469-7998.1996.tb05447.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenology of migration and use of wintering sites by the increasing population of dark‐bellied brent geese Branta bernicla bernicla

Abstract: With 5 figures in the text)During the recovery of the population of dark-bellied brent geese Branru herniclu bernicla, traditional wintering sites in Britain have experienced increases in numbers and new sites have been colonized. Goose counts were used to describe the migration phenology and winter use of Scolt Head, north Norfolk (a traditional site) and the Burry Inlet, South Wales (a relatively new site) over the period of re-colonization and colonization, respectively. During the 1950s, only a few hundred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
3
8
0
Order By: Relevance
“…Thus, unsuccessful individuals departed the colony earlier and, for some colonies, reached their winter destination sooner and spent longer at those destinations, in line with previous findings (Summers et al 1996, Phillips et al 2005, Bogdanova et al 2011). However, our study contrasted with previous work on 1 study population (on the Isle of May), which found a relationship between breeding success and subsequent winter destination, with unsuccessful individuals typically migrating to the NW Atlantic and successful individuals to the northeast Atlantic or North Sea (Bogdanova et al 2011).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Thus, unsuccessful individuals departed the colony earlier and, for some colonies, reached their winter destination sooner and spent longer at those destinations, in line with previous findings (Summers et al 1996, Phillips et al 2005, Bogdanova et al 2011). However, our study contrasted with previous work on 1 study population (on the Isle of May), which found a relationship between breeding success and subsequent winter destination, with unsuccessful individuals typically migrating to the NW Atlantic and successful individuals to the northeast Atlantic or North Sea (Bogdanova et al 2011).…”
Section: Discussionsupporting
confidence: 78%
“…First, we hypothesised that, across colonies, there would be an overall relationship between breeding success and scheduling and location of migration, such that unsuccessful individuals depart the colony earlier, migrate farther, reach their winter destinations sooner and spend longer at those destinations, in line with previous findings in this and other species (Summers et al 1996, Phillips et al 2005, Bogdanova et al 2011. Second, we hypothesised that there would be spatial variation in the strength of carry-over effects among colonies, since variation in environmental conditions among colonies is likely, and more favourable conditions are predicted to dampen carry-over effects (Legagneux et al 2012, Harrison et al 2013).…”
Section: Introductionsupporting
confidence: 56%
“…Thus, the simulated within‐site movements between habitats are consistent with the behaviour of brent geese. At the larger spatial scale of movements throughout Europe, it is well established that the first birds to arrive in western Europe in autumn are generally failed or non‐breeders, with families containing birds of the year arriving sometime later (Summers et al . 1996; Ganter 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that unsuccessful breeders leave the breeding grounds earlier than successful breeders (e.g. [14,16,17]). Although these differences in the timing of departure were associated with wintering periods that were extended for up to several months, there were no apparent differences in winter distribution.…”
Section: Introductionmentioning
confidence: 99%